Foundational Ontology Mediation in ROMULUS - Khan, Zubeida C.; Maria Keet, C. (Knowledge Discovery, Knowledge Engineering and Knowledge Management, 2015)
An approach for semantic interoperability among heterogeneous systems is to assist with the integration of foundational ontologies. In order to achieve this, we have selected three popular foundational ontologies DOLCE, BFO, and GFO, and their related modules. We perform ontology mediation (alignment, mapping, and merging) on these ontologies by aligning their ontology entities using tools, documentation, and our manual alignments, and comparing their effectiveness. Thereafter, based on the alignments, we created mappings in the ontology files resulting and merged ontologies. However, during the mapping process, it was found that structural differences in foundational ontologies, caused by conflicting axioms due to complement and disjointness, and incompatible domain and range restriction, cause logical inconsistencies in foundational ontology alignments, thereby reducing the number of mappings. In this paper, we present each phase of the mediation process, including the mediation issues we encountered with solutions where available.